George Earl Adams, Sr.: The Beginning of a Legacy - Hermesch, Jessica (Kansas State University, The Chapman Center for Rural Studies, 2015)
This bio-essay focuses on the life of George Earl Adams, Sr., a veteran of WWI who returned to farm the family land in Brush Creek Township, Atchison County. George Adams left a legacy of committed military service and family and civic values, represented in the careers of his son and also his grandson, Brigadier General Bruce Adams, both KSU alumni. Research was conducted at the Morse Department of Special Collections in Hale Library, KSU, using the Adams Family Papers; sources also included interviews and exhibits at the Richard B. Myers Hall at KSU.
Jessica Hermesch, “George Earl Adams, Sr.: The Beginning of a Legacy,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/232.
Keywords: 35th Infantry Division; Adams family; Camp Funston; Grasshopper Township; World War I; draft